Business continuity from preparedness to recovery : a standards-based approach - Tucker, Eugene (Buttersworth-Heinemann, 2015)
Business Continuity from Preparedness to Recovery: A Standards-Based Approach details the process for building organizational resiliency and managing Emergency and Business Continuity programs. With over 30 years of experience developing plans that have been tested by fire, floods, and earthquakes, Tucker shows readers how to avoid common traps and ensure a successful program, utilizing, detailed Business Impact Analysis (BIA) questions, continuity strategies and planning considerations for specific business functions. One of the few publications to describe the entire process of business c.